Reducing Energy Intensity and Institutional Environment: A Cross Country Analysis - Suslov, Nikita; Ekaterina, Meltenisova (International Journal of Energy Economics and Policy, 2019)
The article analyses the way the quality of institutions affects the performance of energy saving policies. Based on the analysis of dynamic panel data for 69 countries over the period from 2002 to 2012, using Arellano-Bond approach, we have shown that the elasticity of energy consumption by price of energy depends on institutional factors. We also demonstrated that absolute values of the said indicators are higher in OECD than CIS countries over the whole data sample, which is explained by a higher quality of institutions. Similar valuations and calculations have been produced for the industrial sector as well as the production sphere. The energy consumption in the industrial sector has proved to be more sensitive to the quality of institutions than in production sphere as a whole. We have also performed a general analysis of trends of GDP energy consumption for a number of countries pointing out that a growth of energy prices enhances energy saving processes. Keywords: energy intensity, cross-country analysis, Arellano-Bond approach. JEL Classifications: D02, E02, Q43 DOI: https://doi.org/10.32479/ijeep.8259